82.7k views
3 votes
Solve for x
2(5x+3)=6x-3

User Hosam Aly
by
4.7k points

2 Answers

5 votes

Answer:

x = -9/4

Explanation:

2(5x+3)=6x-3

10x + 6 = 6x - 3

10x - 6x = -3 - 6

4x = -3 - 6

4x = -9

The answer is x = -9/4

User Amjad
by
4.9k points
1 vote

Linear equations

2(5x + 3) = 6x -3

Apply the multiplicative law of distribution.

10x + 6 = 6x - 3

Rearrange the unknown terms on the left side of the equation.

10x - 6x = -3 - 6

Combine as terms

4x = -3 - 6

Calculate the sum or difference.

4x = -9

Divide both sides of the equation by the coefficient of the variable.

x = - 9/4

The answer is x = - 9/4. Because if we do the division, the result is not exact; means that the result is decimal.

User Radha
by
4.4k points